The effectiveness of foreign exchange exposure on improving firms’ financial performance : A case of financial institutions operating in Zanzibar - Omar, Abdalla Mtumwa (Mzumbe University, 2024)
A dissertation report submitted to the School of Business in partial fulfillment the of requirements of Mzumbe University’s Masters Degree in Accounting and Finance